2012
DOI: 10.1177/1362168812436919
|View full text |Cite
|
Sign up to set email alerts
|

How effective are affective activities? Relative benefits of two types of structured input activities as part of a computer-delivered lesson on the Spanish subjunctive

Abstract: Proponents of Processing Instruction (VanPatten, 2005) claim that learners benefit most when presented with both referential and affective structured input activities. Following a classic pretest-posttest design, the present study investigates the role of these two types of activities on the learning of the Spanish subjunctive. Groups differed only with respect to the types of activities completed during practice: (1) affective activities only, (2) referential activities only, or (3) referential activities fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Results indicated an increase in subjunctive recognition rates for all groups and some findings are particularly notable. Because previous research has shown that learners have difficulty with subjunctive production, which does not necessarily increase after periods abroad, but can, however, perform fairly well in mechanical recognition tasks (see, amongst others, Bonilla, 2014;Collentine, 1995Collentine, , 1997Collentine, , 1998Collentine, , 2002Gudmestad, 2012aGudmestad, , 2012bHenshaw, 2013;Isabelli, 2007;Isabelli & Nishida, 2005;Stokes, 1998;Terrell & Hooper, 1974;Terrell et al, 1987) and given participants' prior exposure to mood alternation and the subjunctive mood in various tenses, it was feasible to predict high scores in the pre-test, which was not the case. While it is not surprising that learners were not able to extensively produce subjunctive in the pre-test, not achieving high scores on the recognition component (Control M = 1.50, SD = 1.05, Dictogloss M = 1.69, SD = 1.85, Dictogloss+E = 1.67, SD = 1.77) was not an anticipated outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results indicated an increase in subjunctive recognition rates for all groups and some findings are particularly notable. Because previous research has shown that learners have difficulty with subjunctive production, which does not necessarily increase after periods abroad, but can, however, perform fairly well in mechanical recognition tasks (see, amongst others, Bonilla, 2014;Collentine, 1995Collentine, , 1997Collentine, , 1998Collentine, , 2002Gudmestad, 2012aGudmestad, , 2012bHenshaw, 2013;Isabelli, 2007;Isabelli & Nishida, 2005;Stokes, 1998;Terrell & Hooper, 1974;Terrell et al, 1987) and given participants' prior exposure to mood alternation and the subjunctive mood in various tenses, it was feasible to predict high scores in the pre-test, which was not the case. While it is not surprising that learners were not able to extensively produce subjunctive in the pre-test, not achieving high scores on the recognition component (Control M = 1.50, SD = 1.05, Dictogloss M = 1.69, SD = 1.85, Dictogloss+E = 1.67, SD = 1.77) was not an anticipated outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on L2 Spanish morphosyntactic development including the recognition and production of the subjunctive mood, established that while learners can develop the ability to recognize the subjunctive mood in early stages of interlanguage development and tend to perform well in input-oriented 2 tasks, the ability to produce the subjunctive tends to develop at more advanced stages (Bonilla, 2014;Collentine, 1995Collentine, , 1997Collentine, , 1998Collentine, , 2002Collentine, , 2003Collentine, , 2010Gudmestad, 2012aGudmestad, , 2012bHenshaw, 2013;Stokes, 1988;Terrell & Hooper, 1974;Terrell et al, 1987). Indeed, advanced second language learners (L2ers) show signs of mood production abilities (Bonilla, 2014;Gallego, 2016;Gudmestad, 2012aGudmestad, , 2012b and highly-advanced L2ers display target-like production patterns (Gudmestad, 2012a(Gudmestad, , 2012b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PI, we can distinguish between two types of SI activities: (i) referential, which require learners to deliver an answer that can be judged right or wrong, and (ii) affective, which aim at triggering learners' communicative skills with regards to the target form. Some authors (Marsden and Chen 2011) claimed that referential activities are the only type of activities needed for PI to be successful, while others (Henshaw 2012) reinforced the importance of affective activities in PI. In the present study, I made use of both referential and affective activities.…”
Section: Vanpatten's Input Processing (Ip) Theorymentioning
confidence: 99%
“…The approaches have been as varied as the structures that have been analyzed in previous literature. On the one hand, authors such as Kanwit and Geeslin (2014), Collentine (1995Collentine ( , 1998Collentine ( , 2003Collentine ( , 2010, Sánchez Naranjo (2009), Adrada (2016), VanPatten (2004) Gudmestad (2006Gudmestad ( , 2012Gudmestad ( , 2013, Henshaw (2012), Isabelli and Nishida (2005), and Borgonovo et al (2015) have focused on mood distinction abilities among L2 learners alone. On the other hand, studies including those of Lynch (2008), Montrul (2007Montrul ( , 2008Montrul ( , 2009, Montrul and Perpiñán (2011), Torres (2018), Potowski et al (2009), Mikulski (2010), Correa (2011aCorrea ( , 2011b, and Mikulski and Elola (2013) compared the mood distinction abilities of HL and L2 learners.…”
Section: Introductionmentioning
confidence: 99%